Advantages of the Use of Postbiotics in Poultry Production: A New Concept - M Waqas; NA Nastoh; AA Çinar; MZ Farooq; M Salman (Brazilian Journal of Poultry Science)
ABSTRACT The use of antibiotics has been prohibited in many countries of the world, in response to concerns over the health and welfare concerns of humans and animals. For this reason, scientists have been working on antibiotic alternatives capable of enhancing the productivity and immunity of poultry birds against diseases, as well as the production of healthy and economical poultry meat and eggs. Various alternatives exist and have been used for several decades, such as probiotics, prebiotics, phytobiotics, essential oils, antimicrobial peptides, organic acids, and synbiotics. A relatively new term, “postbiotic,” is used to refer to cell-free supernatants, metabiotics, biogenics, or simply metabolites. It has been suggested that postbiotics are non-viable bacterial products or metabolic byproducts secreted from probiotic microorganisms that have biologic activity in the host. While probiotics are sensitive to heat and oxygen, postbiotics are stable during industrial processing and storage. Postbiotics enhance poultry growth, improve feed efficiency, reduce intestinal pathogens, and promote overall health, making them valuable contributions for sustainable poultry production. They have many important biological properties, such as promoting immunomodulatory, antioxidant, and anti-inflammatory responses. Postbiotics improve intestinal villi, intestinal barrier functions, increase lactic acid production, and reduce Enterobacteriaceae and fecal pH, all of which lead to better immune reaction and health of the gut, as well as superior growth performance. Similarly, postbiotics reduce the plasma cholesterol and triglyceride levels in birds. This review article presents the most recent research investigating the beneficial effects of postbiotics in poultry.